THE THEORETICAL-EMPIRICAL MODEL TO SUPPORT THE MANAGEMENT OF THE IMPLEMENTATION AND SUSTAINABILITY OF ORGANIZATIONAL INNOVATIONS - Kožárová, Mária; Sirotiaková, Mária (International Journal For Research In Business, Management And Accounting, 2019)
Because companies work as a whole and all activities are interconnected, the paper focuses on identifying the most important factors that influence the process of managing the implementation of organizational innovations („OI“). The aim of the paper is to propose a model serving as a support tool for business managers in a complex process of managing the implementation and long-term sustainability of organizational innovations. The model points to the need to coordinate the activities of several business areas, which, in our view, are indispensable for successful management of this process, while stressing the importance of the work of managers. One of its benefits is that it is applicable to different types of subjects. The paper is based not only on the results of research carried out on a sample of 141 Slovak medium and large production companies, but also on professional domestic and foreign literature and a number of studies conducted directly in the business environment.